Side-lobe level reduction in two-dimensional optical phased array antennas - Pita, Julián L.; Aldaya, Ivan [UNESP]; Santana, Octávio J.S.; de Araujo, Lui´s E.E.; Dainese, Paulo; Gabrielli, Lucas H. (Optica Publishing Group, 2018)
We experimentally demonstrate that by arranging the array elements according to Fermat's spiral, the side lobe level of an 8-element SOI-array is reduced by 0:9 dB. Additional experiments show a 6:9 dB reduction for 64-elements.